PENGELOLAAN PEMBELAJARAN DI SD NEGERI 09 HILIA LAMO KAMANG HILIA KECAMATAN KAMANG MAGEK KABUPATEN AGAM - Syukra Vadhillah (IAIN Batusangkar, 2016)
This study was purposed at identifyng the instructional management in State Primary School 09 Hilia Lamo, Kamang Magek, Agam by using qualitative approach case study. The researcher used interview, observation and documentation on collecting data. The results showed that the instructional instrument was made on vacation through workshop 3 until 4 days. The instruction was begun by flight ceremony, morning gymnastics, memorizing and reading a holy quran. The instruction was done by using various methods. To monitor the instructional process, the school gave the notice to the parents related to the students’ skill. Then the teachers were also gotten the suggestion related to teaching improvement through principal’s supervision at least twice a semester.Keywords: Management, Instruction, Primary School, Kamang Magek Agam.